Faktor yang Mempengaruhi Peningkatan Kadar Glukosa Darah Penderita Diabetes Melitus Tipe II di RSUD Kota Sabang - Feri Armansyah; Tiarnida Nababan; Maulia Maulia; Rakhmiyati Rakhmiyati; Tio Abdul Desmawati Ndruru (Malahayati Nursing Journal, 2025)
ABSTRACT Diabetes mellitus (DM) is a syndrome characterized by hyperglycemia and associated abnormalities in carbohydrate, fat, and protein metabolism. These metabolic abnormalities lead to the development of specific forms of renal, ocular, neurologic and cardiovascular complications. The purpose of this study was to determine the factors that influence the increase in blood glucose levels of patients with type II diabetes mellitus. The type of research used is an analytic descriptive survey with a Cross Sectional design. The population in this study were all patients with DM disease at Sabang City Hospital as many as 168 people. The technique of taking subjects using simple random sampling as many as 42 people. Data were collected through direct interviews using a self-administered questionnaire to measure variables. The variables measured were education, knowledge, diet/diit, physical activity/exercise. Variable blood sugar levels of DM patients were measured by direct observation of respondents. The research data analysis was univariate and bivariate analysis with chi square test. The results explained that there was a relationship between education (p = 0.036), knowledge (p = 0.014), diet / diet (p = 0.016), physical activity / exercise (p = 0.043) and obesity (p = 0.000) with an increase in blood glucose levels of patients with DM. The conclusion of this study is that there is a relationship between education, knowledge, diet/diet, physical activity/exercise and obesity with increased blood glucose levels of patients with DM. It is recommended for further research by analyzing the relationship between hormone levels such as thyroid, cortisol, or reproductive hormones (estrogen/testosterone) with blood sugar control.  Keywords: Education, Knowledge, Diet/Diit, Physical Activity/Exercise, Obesity, Diabetes Mellitus  ABSTRAK Diabetes Mellitus (DM) merupakan sindrom yang ditandai oleh adanya hiperglikemia dan berkaitan dengan abnormalitas metabolisme karbohidrat, lemak, dan protein. Abnormalitas metabolik ini mengarak pada perkembangan bentuk spesifik dari komplikasi ginjal, okular, neurologik dan kardiovaskular. Tujuan penelitian ini adalah untuk mengetahui Faktor Yang Mempengaruhi peningkatan Kadar Glukosa Darah Penderita Diabetes Melitus Tipe II. Jenis penelitian yang digunakan adalah survei bersifat deskriptif analitik dengan rancangan Cross Sectional. Populasi dalam penelitian ini adalah seluruh pasien dengan penyakit DM di RSUD Kota Sabang sebanyak 168 orang. Teknik pengambilan subjek menggunakan simple random sampling sebanyak 42 orang. Data dikumpulkan melalui wawancara langsung menggunakan kuesioner yang disusun sendiri untuk mengukur variabel. Variabel yang diukur adalah  pendidikan, pengetahuan, pola makan/diit, aktivitas fisik/olahraga. Variabel kadar gula darah penderita DM diukur dengan observasi langsung pada responden. Analisa data penelitian adalah analisis univariat dan bivariat dengan uji chi square. Hasil penelitian menjelaskan terdapat hubungan antara pendidikan (p= 0,036), pengetahuan (p= 0,014), pola makan/diit (p= 0,016), aktivitas fisik/olahraga (p= 0,043) dan obesitas (p= 0,000) dengan peningkatan kadar glukosa darah penderita DM. Kesimpulan penelitian ini adalah terdapat hubungan antara Pendidikan, pengetahuan, pola makan/diie, aktivitas fisik/olahraga dan obesitas dengan peningkatan kadar glukosa darah penderita DM. Disarankan untuk penelitian lanjutan dengan menganalisis hubungan antara kadar hormon seperti tiroid, kortisol, atau hormon reproduksi (estrogen/testosteron) dengan kontrol gula darah. Kata Kunci: Pendidikan, Pengetahuan, Pola Makan/Diit, Aktivitas Fisik/Olahraga, Obesitas, Diabetes Mellitus